2008
DOI: 10.3899/jrheum.080375
|View full text |Cite
|
Sign up to set email alerts
|

The Minimally Important Difference for the Fatigue Visual Analog Scale in Patients with Rheumatoid Arthritis Followed in an Academic Clinical Practice

Abstract: Introduction Fatigue is a common symptom in RA and used as an outcome measure in RA clinical trials. We studied a large academic clinical practice to estimate the minimally important difference (MID) for a fatigue visual analog scale using patient-reported anchors (fatigue, pain and overall health). Methods RA patients (N=307) had clinic visits at 2 time points at a median of 5.9 months apart. They completed fatigue visual analog scale (VAS; 0–10) and retrospective anchor items, “How would you describe your … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 19 publications
13
70
0
Order By: Relevance
“…The players experienced an increase in VAS fatigue 1.17 to 2.83 during the games. The published MCID for VAS fatigue is 0.82 to 1.13 [13]. Finally, the players experienced an increase in exertion with Borg scale of 1.82 during the game at the end of the season, and the MCID for Borg scale is 1 [19] showing our results were statistically and clinically significant.…”
Section: Discussionsupporting
confidence: 52%
“…The players experienced an increase in VAS fatigue 1.17 to 2.83 during the games. The published MCID for VAS fatigue is 0.82 to 1.13 [13]. Finally, the players experienced an increase in exertion with Borg scale of 1.82 during the game at the end of the season, and the MCID for Borg scale is 1 [19] showing our results were statistically and clinically significant.…”
Section: Discussionsupporting
confidence: 52%
“…Studies using statistically based measures to determine values that exceed random variation, such as SDD or reliable change index, consistently report higher values than those that report MCID. This is best illustrated by a study of fatigue in patients with RA that reported both MCID and reliable change index 7. The MCID for improvement in fatigue in this study was 0.82 to 1.12, while the reliable change index was 3.47.…”
Section: Discussionmentioning
confidence: 58%
“…The goal of MCID assessments is to identify the smallest change perceived as beneficial by patients 5, whereas the d crit method is based on the premise that significant individual responses should, at minimum, result in changes that exceed within‐subject, measurement‐associated variability over periods of time relevant to a clinical setting 4. In this respect, the d crit method is similar to assessments of the smallest detectable difference (SDD) 6 or the reliable change index 7. However, these latter assessments are usually based on reliability constants derived from measurements made over a short period of time, rather than over a period of months to a year, a time frame that is more relevant to assessment of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue (VAS) [7] and short-form-36 (SF-36) [8] were assessed at baseline, weeks 36, 48, and 76, and then every 24 weeks throughout the OLE. Continuous measures are reported as absolute values or mean changes from RCT baseline.…”
Section: Efficacy Evaluationsmentioning
confidence: 99%